Efeito da fragmentação de habitat sobre a riqueza de espécies arbustivo arbóreas do cerrado sensu stricto, no município de Uberlândia, Minas Gerais - Carmo, Adenilza Borges do (2006)
The main this study was investigate how may shrub-woody species richness be the effected by sensu stricto cerrado fragmentation. We hypothesized that species richness may be influenced by size, fragment shape and degree isolament, with zoocoric species being more strongly affected by fragmentation. The Landsat 7 satellite image (11/out./2002) was used to produce digitized maps of each fragment. The land use and land cover maps were produced using in the program SPRING 4.1 and the fragmentation index area, perimeter, shape, distances to nearest neighbor and isolation were determined for each fragment. The floristic inventories were conducted in a total of nine cerrado fragments. In each fragment 50 plots were established. All individuals com CAP > 15cm were identified and their height and perimeter were measured in 50 plots of 10 x 10m. To the individuals with CAP <15cm and > 1m height the plots of 10 x 10m were subdivided in plots of 5 x 10m and all individuals were identified and counted in these. A total of 16.714 individuals belonging to in 170 species, 107 generous and 50 botanical families was surveyed in the nine cerrado fragment studied. The multiple linear regression indicated that the richness shrub-woody species was affected by fragment area, but not by fragment shape and degree of isolation. Negative relationship was founded between percentage of autocoric species and fragment size (rs= -0,790), and isolation was correlated with the percentage of zoocoric species (rs = 0,755). The percentage of autocoric individual was negatively correlated with shape fragmen (r = -0,719). Anemocory did not relationship with the other variables considered this study. This study suggests that larger fragments are necessary to conservation of shrub and tree species of the sensu stricto cerrado, however, small fragments are also important elements of the landscape because increase the connection between fragments or areas of continuous habitat.